Dataset and measurements from a current density sensor during experimental testing of dynamic load cycling for a parallel-serpentine design of a proton exchange membrane fuel cell - Baltasar Toharias; Christian Suárez; Alfredo Iranzo; María Salva; Felipe Rosa (Data in Brief, 2024)
A dataset from experimental tests of a proton exchange membrane fuel cell (PEMFC) with an active area of approximately 50 cm2, parallel-serpentine channels and cross-flow field distribution between anode and cathode is presented. Tests were performed for four different gas inlet and outlet configurations. In particular, tests were performed for the original configuration, hydrogen inlet and outlet reversed, air inlet and outlet reversed, and hoses reversed for both gases. The operating conditions for all gas configurations were: pressure of 0.5 bar, temperature of 65 °C, anode and cathode relative humidity of 60 %, and anode and cathode stoichiometry of 1.3 and 2.5 respectively. The tests performed were the polarization curve (PC) for each gas configuration and the dynamic load cycles (FC-DLC) also for each hose position. A current density mapping (CDM) sensor, capable of measuring both the current density distribution and the temperature distribution inside the cell, was inserted into the fuel cell system during all tests. The use of the sensor during the experiments makes it possible to know how these distributions behave and to observe whether or not there is homogeneity in its measurements, thus verifying that the design of the flow channels is adequate and fulfilling its function. The results can be used to investigate and compare other bipolar plates and channel designs, or to compare with results from other test benches and environmental conditions.